Da afirmação étnica à luta pela garantia da terra: a história de luta do povo indígena kokama, aldeia porto praia de baixo, município de Tefé- Amazonas - Silva, Francisca Cardoso (2019)
This work sought to address the process of affirming ethnic identity and the struggle for the territory of the Porto Praia de Baixo village, the Kokama indigenous people, a process that has been taking place in the Middle Rio Solimões region in recent years, which according to data from the Union of indigenous peoples of the middle Solimões e affluentes- UNIPI / MSA, between 2000 and 2018, there are approximately 45 communities that are ethnically affirming themselves and claiming ethnic and territorial recognition by FUNAI, with an average of three requests per year for land demarcation in the region. The research had as main objective: To analyze the meanings involved in the process of affirmation and ethnic recognition of the Kokama indigenous people, from the Porto Praia de Baixo village and the paths already taken by the people for the legal guarantee of the land. And as a methodology we use oral history to carry out the interviews, bibliographic review and document analysis.